PENGARUH APLIKASI ASAP CAIR CANGKANG KELAPA SAWIT PADA TANDAN BUAH SEGAR TERHADAP KUALITAS MUTU CPO (CRUDE PALM OIL) - Ramadhani, Edo; Giyanto, Giyanto; Purwanto, Her (Institut Teknologi Sawit Indonesia (ITSI), 2022)
The results showed that liquid smoke grade 2 of palm oil shells were able to reduce the content of free fatty acids in crude palm oil. The results of the best free fatty acid levels found in the sample of the spray treatment method decreased by 0.38% and the combination decreased by 0.52%, the results obtained were greatly decreased and met the Indonesian National Standard 01-2901-2006. The water content and dirt content produced are still very high, the lowest average water content is obtained by sample B2 with a result of 0.94% and the highest average result is obtained by sample A, which is 0.99% and the result of dirt content with an average result The lowest average was obtained by sample B with a result of 1.38% and the highest average result was obtained by sample B2 with an average result of 4.2%. The results of high water content and dirt content were caused by obtaining crude palm oil by pressing using a manual tool with a cloth so the results obtained did not meet the Indonesian National Standard 01-2901-2006, namely 0.5%. Then the results of DOBI levels (Deterioritation Of Bleachability Index) were obtained with the lowest result of 2.56 from the results of sample B1 and the highest result of 2.25 ppm from the results of B3, if it is associated with the quality of the oil obtained is still not sufficient, it is still not meeting the standards set. determined by PORIM (Palm Oil Research Institute of Malaysia) which is 2.36 – 3.24. For the level of carotene produced, it is still not enough, namely, the lowest average result is 4.26 ppm from sample B3 and the highest average result is obtained by sample A, which is 488 ppm, so it still does not meet the quality standards of carotene parameters according to Palm Oil Refiners. Association of Malaysia (PORAM) which is 500 - 700 ppm.